Open Source Technologies - Gottinger, Hans W. (Advances in Social Sciences Research Journal, 2017)
Abstract. We focus on a contestable market with network externalities with an incumbent and an entrant. The incumbent, unlike the entrant, already has an installed base of consumers. We look at decision situations of firms regarding how proprietary they want to make their technology , either through patent protection or through development in open source systems (OSS). We explicitly model the direct and indirect effects of network externalities. For example, more software companies are willing to produce programs for an operating system (OS) if it has a larger consumer base. This increased competition could lead to an improvement of the quality of the OS. The model predicts that using open source technologies is likely to enhance the rate of R&D , and consequently the quality of the product.. An incumbent that would choose this strategy is likely to deter entrance of a newcomer because it can play out its advantage of a larger network.